Reshaping Urbanization in Rwanda : Profiling Secondary Cities in Rwanda—Dynamics and Opportunities - World Bank Group (World Bank, Washington, DC, 2017)
Reshaping Urbanization in Rwanda: Economic and Spatial Trends and Proposals is an Advisory Services and Analytics (ASA), jointly provided by the Poverty and Equity Global Practice and the Social, Urban, Rural and Resilience Global Practice at the World Bank. The objective of this report is to inform the Government’s policies and strategies on urbanization as a driver of economic development, job creation, and poverty reduction, through the following four stand‐alone but closely related notes. Stimulating urban economic development, particularly outside the capital city of Kigali, is critical to helping Rwanda to achieve its strategic objective of a 35 percent urban population share by 2020. This note looks at the current growth rates and characteristics of secondary cities1 and other fast‐growing towns outside of Kigali, and assesses the opportunities and prospects for, as well as constraints upon, future economic growth and development. It also sets out key actions required from the Government of Rwanda (GoR) tohelp stimulate growth in these cities and towns. There are multiple population estimates for secondary cities and fast‐growing towns due to the inconsistencies in defining which areas are urban and in defining city boundaries, and thus which sectors to include in estimates of city populations. According to the 2002 and 2012 censuses, the six secondary cities grew at an average rate of 3.3 percent over this period, slower than the national rate of urban growth of 4.1 percent and the rate for Kigali of 4.2 percent. In comparison, the three fast‐growing towns are estimated to have grown at a rate of 5.3 percent, albeit from a lower starting base, between 2002 and 2012. Of the secondary cities, Musanze, Rubavu and Nyagatare are growing most rapidly. The Musanze to Rubavu corridor benefits from (i) the rich agricultural resources along this corridor, and (ii) Rubavu’s proximity to the large market of Goma in DRC. Nyagatare has absorbed significant investment in recent years, and has also benefitted from the high levels of migration to the East of the country witnessed by the most recent inter‐censual period. This is reflected in the findings of Note 2 which identifies internal migration toward the Eastern Province.